Factors Affecting Earnings Management in the Food and Beverage Sector Listed on the Indonesia Stock Exchange - Rudy*, Ryan Pahlawan; Hady, Hamdy; Nalurita, Febria (Universitas Syiah Kuala, 2023)
The purpose of this study was to analyze the factors that influence earnings management in the food and beverage sector listed on the Indonesia Stock Exchange, namely corporate governance, company performance, and corporate social responsibility. The design of this study is descriptive exploratory research to see indications of the influence of corporate governance, corporate performance, and corporate social responsibility on corporate earnings management. The research sample includes as many as 34 manufacturing companies in the food and beverage sector. The data analysis method used in this study is panel data regression. The available data was tested using E-Views 10.0 software. The results showed that there was no effect of corporate governance on firm performance, there was no effect of corporate governance on earnings management, there was an effect of corporate responsibility on corporate responsibility, there was a negative effect on firm performance on earnings management, there was a positive influence on corporate responsibility on earnings management, there is a negative effect of corporate governance on earnings management that is mediated by corporate performance, and there is no significant influence of corporate governance on earnings management that is mediated by corporate responsibility. Research implications: corporate governance should pay attention to earnings management by considering company performance, corporate governance, and corporate responsibility. This research can be used as a basis for developing previous research to obtain empirical evidence about the factors that influence earnings management.